The method of corrosion crack opening evaluation for the reinforced concrete structures technical state assessment - V.B. Stepanov (Инженерно-строительный журнал, 2012)
The problem of the reinforced concrete structures technical state assessment assumes the improvement of techniques of their nondestructive control. Therefore, the technique based on criterion of integral values of the crack opening width is proposed.This criterion can serve as independent parameter of corrosion damage. Average value of crack width allows estimating thickness of corrosion products for determination residual bond between concrete and reinforcement.The comparative analysis with a standard technique of measurement is carried out. Shortcomings of maximum crack width as a parameter of serviceability are shown. The integrated technique does possible correction, taking into account nonlinearity of a crack, size of concrete layer, excludes manifestation of the methodical and subjective errors peculiar to a standard technique of measurement.